Fiscal Policy, Growth and Convergence in Europe - Norman Gemmell; Richard Kneller (New Zealand Government, The Treasury, 2003)
Recent evidence on the impact of fiscal policy – taxes, public expenditures and budget deficits – on long-run growth in OECD countries has adopted the Barro (1990) framework to distinguish between `productive' and `unproductive' expenditures, and `distortionary' and `non-distortionary' taxes. Using estimated long-run growth effects from these fiscal variables, this paper simulates the effects on growth rates of observed fiscal policy changes in the EU. With two exceptions, the individual country growth effects of actual changes in taxes, expenditures and deficits appear plausible at around –0.3 to +0.3 of a percentage point per annum. Few common policy scenarios are apparent in the data however, with key sources of differences between countries being the extent to which distortionary taxes or deficits were used to fund public spending increases and whether additional spending was focussed on `productive' activities. One implication of our results is that the change in the overall share of taxes or spending in GDP or the annual budget surplus/deficit is not a good guide to whether the growth effects of fiscal policy are likely to be positive or negative. The paper also considers whether our growth regression model, which imposes parameter homogeneity across countries, is justified. The evidence suggests this is the case, with a high degree of uniformity across countries. Finally the paper considers whether there is any evidence of `fiscal convergence' across the EU. That is, are growth-affecting fiscal variables becoming more similar over time across the EU? Though data are limited, the answer to this question appears to be negative, with little evidence of unconditional convergence. Countries' tax or expenditure/GDP ratios do, however, generally revert towards their steady-state paths.
Keywords: H20; H30; 330; Fiscal policy; growth; convergence; taxation; public expenditure